Dextromethorphan Suppresses Lipopolysaccharide-Induced Epigenetic Histone Regulation in the Tumor Necrosis Factor-α Expression in Primary Rat Microglia. (8th December 2020) - Yang, Yung-Ning; Yang, Yu-Chen S. H.; Wu, Pei-Ling; Yang, Chun-Hwa; Kuo, Kuang-Che; Yang, San-Nan
Abstract : The activation of microglial cells plays an important role in the cascade of events leading to inflammation-mediated neurodegenerative disorders. Precision therapeutics require that adjunctively feasible drugs be found to prevent microglial cell activation and prevent inflammation-mediated neuronal injury. Dextromethorphan (DM) has been reported to possess neuroprotective effects in lipopolysaccharide- (LPS-) stimulated animals; however, it remains unclear whether epigenetic regulatory mechanisms in microglial cells are involved in such DM-mediated neuroprotective effects. In this study, DM simultaneously suppressed LPS-induced activation of tumor necrosis factor- (TNF-) α expression and subsequent caspase-3 signaling in primary microglial cells associated with notable morphological changes. Furthermore, therapeutic action sites of DM involved differential enhanced trimethylation of H3K4 modifications in the promoter region of tnf - α gene locus in primary microglial cells. In summary, DM may exert neuroprotective and anti-inflammatory effects through differential epigenetic histone modifications of TNF- α expression in microglial cells and might therefore raise the possibility of providing an adjunctively beneficial role for a tentative therapeutic strategy in neurodegenerative diseases resulting from inflammation.